Sentiment Analysis of Public Comments on Coldplay Concerts on Twitter Using the Naïve Bayes Method - Dwisyahputra, Achmad Adbillah; Kurniawan, Rakhmat (Journal of Computer Networks, Architecture and High Performance Computing, 2024)
Social media platform Twitter had become one of the most popular platforms for communication and information sharing. In the context of entertainment events such as music concerts, Twitter became a bustling place with various comments and opinions from the public regarding their experiences attending a concert. Many fans shared their experiences about Coldplay concerts on Twitter. These comments were highly varied and required a thorough understanding to interpret the overall public sentiment. Event organizers and Coldplay's band managers needed to understand public feelings about their concerts. This information was crucial for the evaluation and improvement of future events. Comments on Twitter were often brief and diverse, making manual data processing inefficient and necessitating automated tools to understand the sentiment within them. Sentiment analysis, or opinion mining, was the process used to understand, extract, and process text data automatically to gather information about the sentiment contained in opinion sentences. Research on sentiment analysis frequently focused on opinions that contained positive or negative sentiments. To classify these positive and negative sentiments, the Naive Bayes (NB) classification method was employed. The purpose of this study was to analyze the sentiment of public comments about Coldplay concerts on Twitter using the Naive Bayes method. The expected outcome was to provide insights into public sentiment towards Coldplay concerts, which would be valuable for event organizers and the band's managers in evaluating and improving future events.